Mesure des risques de victimisation associés à la pratique clinique auprès des détenus fédéraux - Lusignan, Richard (Psychiatrie et violence)

(untitled) (Institut Philippe-Pinel de Montréal, 2000)
This article focuses on three questions related to the risks of criminal victimization encountered by clinicians in criminology: 1) what are the general incidence, prevalence and forms of victimization in this profession? 2) Does victimization occur mostly in work settings or during any other routine activity? 3) Are these events of victimization stable across time or within the individual's career?Statistically, two main patterns emerge: violent incidents occur in works settings (mostly assaults, assaults with a weapon, illegal confinements) while non-violent events happen outside of occupational settings. In the case of our respondents, between 1976 and 1990, our results show that the risks of criminal victimization were increased by a factor of 33% merely by being clinicians in the field of criminology. Theoretical explanations are drawn from the routine activity model (Cohen and Felson, 1979) and the construction process of social problems (Spector and Kitsuse, 1977).